REFLEKSI PENDIDIKAN DALAM PERSPEKTIF FILSAFAT IDEALISME - Suripto, Suripto (EDUKASI: Jurnal Pendidikan Islam, 2016)
Philosophy as the mother of knowledge has large contributed to develop of education. Through a profound point of view, the philosophy of trying to parse its education up to its roots in order to obtain a comprehensive view. The philosophy of Platos Idealism that further emphasizes the importance of the superiority of the mind, the spirit or the soul of the things that is material. Leaves from the trees thoughts of philosophy of idealism which consists of view of metaphysics, epistimologi and gives its own perspective of axiology in philosophical analysis of the world education is again reflected in his views about the human being, the formulation of the purpose of education, curriculum, methods, pupils and teachers.